The CARMA Study: Early Infant Antiretroviral Therapy—Timing Impacts on Total HIV-1 DNA Quantitation 12 Years Later. (17th July 2020) - Foster, Caroline; Domínguez-Rodríguez, Sara; Tagarro, Alfredo; Gkouleli, Triantafylia; Heaney, Judith; Watters, Sarah; Bamford, Alasdair; Fidler, Katy; Navarro, Marisa; De Rossi, Anita; Palma, Paolo; Nastouli, Eleni; et al.
Abstract: Background: Strategies aimed at antiretroviral therapy (ART)–free remission will target individuals with a limited viral reservoir. We investigated factors associated with low reservoir measured as total human immunodeficiency virus type 1 (HIV-1) DNA in peripheral blood mononuclear cells (PBMCs) in perinatal infection (PaHIV). Methods: Children from 7 European centers in the Early Treated Perinatally HIV Infected Individuals: Improving Children's Actual Life (EPIICAL) consortium who commenced ART aged <2 years, and remained suppressed (viral load [VL] <50 copies/mL) for >5 years were included. Total HIV-1 DNA was measured by quantitative polymerase chain reaction per million PBMCs. Factors associated with total HIV-1 DNA were analyzed using generalized additive models. Age, VL at ART initiation, and baseline CD4% effects were tested including smoothing splines to test nonlinear association. Results: Forty PaHIV, 27 (67.5%) female 21 (52.5%) Black/Black African, had total HIV-1 DNA measured; median 12 (IQR, 7.3–15.4) years after ART initiation. Eleven had total HIV-1 DNA <10 copies/10 6 PBMCs. HIV-1 DNA levels were positively associated with age and VL at ART initiation, baseline CD4%, and Western blot antibody score. Age at ART initiation presented a linear association (coefficient = 0.10 ± 0.001, P ≤ .001), the effect of VL (coefficient = 0.35 ± 0.1, P ≤ .001) noticeable >6 logs. The effect of CD4% (coefficient = 0.03 ± 0.01, P = .049) was not maintained >40%. Conclusions: In this PaHIV cohort, reduced total HIV-1 DNA levels were associated with younger age and lower VL at ART initiation. The impact of early-infant treatment on reservoir size persists after a decade of suppressive therapy. Abstract : Initiation of antiretroviral therapy at a younger age and lower plasma viral load were associated with a lower HIV-1 viral reservoir in peripheral blood mononuclear cells after more than a decade of sustained virological suppression.